Loading Time Flexibility in Cross-docking Systems - Konur, Dinçer; Golias, Mihalis (My University, 2017)
In this study, we investigate truck-to-door assignment problem for loading outgoing trucks in a cross-docking system with flexible handling times. Specifically, a truck's loading time depends on the number of workers assigned to the outbound door, where the truck is being loaded. An optimization problem is formulated to jointly determine the number of workers and the trucks to be loaded at each door. The resulting problem is a nonlinear integer programming model. Due to the complexity of this model, two evolutionary heuristic methods are proposed for solution. First heuristic method is based on truck assignments while the second heuristic is based on worker assignments. A numerical study is conducted to compare the two heuristic methods.
Keywords: Cross-docking; Flexibility; Heuristics